Negative electrode sheet, electrochemical device, and electronic apparatus

By designing a negative electrode sheet with a specific specific table decreasing rate and porosity porosity, combined with graphite material and binder ratio, the shortcomings of lithium-ion batteries in discharge capacity, fast charging performance and cycle performance are solved, and excellent electrical power is achieved Chemical properties.

CN119400805APending Publication Date: 2025-02-07ENVISION AESC JAPAN LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411585429.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing lithium-ion batteries containing graphite materials cannot guarantee excellent discharge capacity, fast charging performance and cycling performance.

Method used

By designing a negative electrode sheet, the decreasing rate P0 of the specific table is between 12% and 18%, and the porosity ε of the electrode sheet is more than 13%. Combined with the specific graphite material and binder ratio, excellent electrochemical performance is formed .

Benefits of technology

It achieves excellent performance in discharge capacity, fast charging performance and cycling performance of lithium-ion batteries, and takes into account energy density, cycling performance and storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_21
    Figure SMS_21
  • Figure SMS_22
    Figure SMS_22
  • Figure SMS_23
    Figure SMS_23
Patent Text Reader

Abstract

The invention discloses a negative plate, an electrochemical device and electronic equipment. The specific surface declining rate P0 of the negative plate is 12%-18%; wherein P0 = 1-P, and P is the ratio of the specific surface area of the negative plate under the second compaction to the specific surface area of the negative plate under the first compaction; the pole piece porosity epsilon of the negative pole piece is more than 13%, wherein the pole piece porosity is the pole piece porosity of the negative pole piece under the second compaction. An electrochemical device (especially a lithium ion battery) containing the composite material can ensure excellent discharge capacity, fast charge performance and cycle performance, and also has excellent energy density, cycle performance and storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a negative electrode sheet, an electrochemical device and an electronic device. Background Art

[0002] Conventional natural graphite, such as flake graphite, has the characteristics of high capacity and high pressure density, but it is usually difficult to apply in practice due to its own defects. The capacity of artificial graphite is difficult to exceed 360mAh / g, and it is difficult to exceed 1.70g / cc when it is made into a pole piece. Even if it is forced to do so, the dynamics will be extremely poor. Compared with conventional natural graphite and artificial graphite, microcrystalline natural graphite has the intrinsic characteristics of high capacity and good dynamics, and has excellent application prospects in high-capacity fast-charging lithium-ion batteries.

[0003] Chinese patent application CN 110380050A uses asphalt impregnation filling to improve the intrinsic powder pressure of microcrystalline graphite, but this treatment will reduce the pores of the material itself, greatly deteriorate the dynamics of the material itself, and has limited effect on the compaction of the pole piece at the pole piece compaction level, and the lithium-ion battery containing it cannot guarantee excellent discharge capacity, fast charging performance and cycle performance. Therefore, it is crucial to achieve excellent discharge capacity, fast charging performance and cycle performance for lithium-ion batteries using graphite materials as negative electrode materials. Summary of the invention

[0004] In order to solve the defect that the existing lithium-ion batteries containing graphite materials cannot guarantee excellent discharge capacity, fast charging performance and cycle performance, the present invention provides a negative electrode sheet, an electrochemical device and an electronic device. The electrochemical device (especially the lithium-ion battery) containing the negative electrode sheet can guarantee excellent discharge capacity, fast charging performance and cycle performance, and also take into account excellent energy density, cycle performance and storage performance.

[0005] To achieve the above objectives, the present invention adopts the following technical solutions.

[0006] In a first aspect, the present invention provides a negative electrode sheet, wherein the specific surface area decrease rate P0 of the negative electrode sheet is 12%-18%; wherein P0=1-P, P is the ratio of the specific surface area of ​​the negative electrode sheet under the second compaction to the specific surface area of ​​the negative electrode sheet under the first compaction;

[0007] The electrode porosity ε of the negative electrode sheet is greater than 13%, wherein the electrode porosity is the electrode porosity of the negative electrode sheet under the second compaction;

[0008] The second density is 1.80 g / cc or the ultimate density of the negative electrode sheet; the first density is 1.65 g / cc.

[0009] In a second aspect, the present invention provides an electrochemical device comprising the negative electrode sheet as described above.

[0010] In a third aspect, the present invention provides an electronic device comprising the electrochemical device as described above.

[0011] The positive and progressive effects of the present invention are:

[0012] The present invention provides a negative electrode sheet. By controlling and designing parameters such as the specific surface decrease rate of the negative electrode sheet and the electrode sheet porosity of the negative electrode sheet under 1.80 g / cc compression, an electrochemical device (especially a lithium ion battery) including the negative electrode sheet can ensure excellent discharge capacity, fast charging performance and cycle performance, and take into account excellent energy density, cycle performance and storage performance. DETAILED DESCRIPTION

[0013] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0014] Negative plate

[0015] In the negative electrode sheet provided in the first aspect of the present invention, the specific surface area decrease rate P0 of the negative electrode sheet is 12%-18%; wherein P0=1-P, P is the ratio of the specific surface area of ​​the negative electrode sheet under the second compaction to the specific surface area of ​​the negative electrode sheet under the first compaction;

[0016] The electrode porosity ε of the negative electrode sheet is greater than 13%, wherein the electrode porosity is the electrode porosity of the negative electrode sheet under the second compaction;

[0017] The second density is 1.80 g / cc or the ultimate density of the negative electrode sheet; the first density is 1.65 g / cc.

[0018] In the present invention, the specific surface area of ​​the negative electrode sheet is obtained by testing according to the national standard GB / T 19587-2017.

[0019] In the present invention, the "negative electrode sheet under the second compaction" can be obtained by the following method A or B:

[0020] Method A: Press the negative electrode sheet to a density of 1.80 g.cc without lithium insertion. -1 , the negative electrode sheet has a good appearance and no wavy wrinkles on the edge;

[0021] Method B: Press the negative electrode sheet to the limit density without lithium insertion. The negative electrode sheet has a good appearance and no wavy edges. At this time, the limit density is less than 1.80 g.cc -1 .

[0022] In the present invention, the "negative electrode sheet under the first compaction" can be obtained by the following method: the negative electrode sheet is pressed in a non-lithium-inserted state until the compaction is 1.65 g.cc -1 The negative electrode has a good appearance and no wavy edges.

[0023] In the present invention, the specific surface decrease rate of the negative electrode sheet is a comprehensive result of the particle orientation, tortuosity and inter-particle pores in the negative electrode sheet, and reflects the ability of the negative electrode sheet to maintain similar particle orientation, tortuosity and inter-particle pores under extremely high pressure density as under conventional density. The smaller the specific surface decrease rate of the negative electrode sheet, the more stable the structure of the negative electrode sheet; if the specific surface decrease rate of the negative electrode sheet is too small, it means that the hardness of the negative electrode sheet is too large and it is difficult to deform, which will affect the density of the negative electrode sheet.

[0024] In some preferred embodiments, the specific table decline rate of the negative electrode sheet is 13%-17%; the specific table decline rate of the negative electrode sheet is, for example, 12.5%, 12.7%, 13.2%, 13.3%, 13.5%, 13.7%, 13.9%, 14.1%, 14.5%, 14.7%, 14.9%, 15%, 15.2%, 15.3%, 15.9%, 16.4%, 16.7%, 17.2%, 17.7% or 17.8%.

[0025] In the present invention, the electrode porosity of the negative electrode sheet refers to the ratio of the volume of pores in the negative electrode sheet to the apparent volume of the negative electrode sheet.

[0026] In the present invention, the porosity of the pole piece can be obtained by testing according to the national standard GB21650.1-2008.

[0027] In some preferred embodiments, the porosity of the negative electrode sheet is 18%-26%, for example, 18.2%, 19.3%, 20.5%, 20.6%, 20.9%, 21.2%, 22.2%, 22.5%, 22.7%, 23.1%, 23.2%, 23.5%, 23.6%, 23.9%, 24.1%, 24.2%, 24.3%, 25.2% or 25.6%.

[0028] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 14.7%, and the electrode porosity of the negative electrode sheet is 23.6%.

[0029] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 12.5%, and the electrode porosity of the negative electrode sheet is 25.2%.

[0030] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 17.8%, and the electrode porosity of the negative electrode sheet is 19.3%.

[0031] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 13.2%, and the electrode porosity of the negative electrode sheet is 24.1%.

[0032] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 15.9%, and the electrode porosity of the negative electrode sheet is 22.2%.

[0033] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 13.9%, and the electrode porosity of the negative electrode sheet is 23.9%.

[0034] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 13.5%, and the electrode porosity of the negative electrode sheet is 24.3%.

[0035] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 16.4%, and the electrode porosity of the negative electrode sheet is 20.5%.

[0036] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 14.1%, and the electrode porosity of the negative electrode sheet is 23.9%.

[0037] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 15.2%, and the electrode porosity of the negative electrode sheet is 24.2%.

[0038] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 13.3%, and the electrode porosity of the negative electrode sheet is 21.2%.

[0039] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 17.2%, and the electrode porosity of the negative electrode sheet is 20.6%.

[0040] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 12.7%, and the electrode porosity of the negative electrode sheet is 22.5%.

[0041] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 12%, and the electrode porosity of the negative electrode sheet is 25.6%.

[0042] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 13.7%, and the electrode porosity of the negative electrode sheet is 23.2%.

[0043] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 16.7%, and the electrode porosity of the negative electrode sheet is 20.9%.

[0044] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 17.7%, and the electrode porosity of the negative electrode sheet is 18.2%.

[0045] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 15.3%, and the electrode porosity of the negative electrode sheet is 22.7%.

[0046] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 15%, and the electrode porosity of the negative electrode sheet is 23.1%.

[0047] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 14.9%, and the electrode porosity of the negative electrode sheet is 23.5%.

[0048] In a specific embodiment, the negative electrode sheet satisfies: the specific surface decreasing rate of the negative electrode sheet is 14.5%, and the electrode porosity of the negative electrode sheet is 23.1%.

[0049] In the present invention, the bonding force F of the negative electrode sheet is N Refers to the connection strength between the active material layer and the current collector in the negative electrode sheet.

[0050] In some optional embodiments, the bonding force F of the negative electrode sheet is N 25-50 N, for example 27 N, 28 N, 31 N, 32 N, 33 N, 34 N, 35 N, 38 N, 39 N, 40 N, 41 N, 43 N or 45 N.

[0051] In the present invention, the bonding strength of the negative electrode sheet is tested according to the following method: the negative electrode sheet to be tested is cut into a long strip (length × width = 10 cm × 3 cm), and is bonded to a long strip of quartz glass plate (slightly larger in area than the negative electrode sheet) with VHB tape. The negative electrode sheet is repeatedly rolled three times with a special small round roller to ensure that the negative electrode sheet is fully bonded to the VHB. A universal stretching machine is used, and the standard method of measuring bonding strength at 180° is selected to test the bonding strength of the negative electrode sheet. Each sample is tested three times and the average value is taken.

[0052] In an optional embodiment, the negative electrode sheet includes a negative electrode current collector, a first active material layer is arranged on at least one surface of the negative electrode current collector, a second active material layer is arranged on the first active material layer, the first active material layer includes a first graphite material and a first binder, the second active material layer includes a second graphite material and a second binder, and the Dv50 particle size of the first graphite material is larger than the Dv50 particle size of the second graphite material.

[0053] In a preferred embodiment, the difference between the Dv50 particle size of the first graphite material and the Dv50 particle size of the second graphite material is 3-7 μm, preferably 4.5-5.5 μm, for example 5 μm.

[0054] In a preferred embodiment, the particle crushing force F1 of the first graphite material is 30-36 mN, for example, 31 mN, 33 mN, 34 mN or 35 mN.

[0055] In a preferred embodiment, the particle crushing force F2 of the second graphite material is 20-30 mN, for example, 22 mN, 24 mN or 27 mN.

[0056] In the present invention, the particle crushing force refers to the critical pressure at which a single particle of a material breaks when undergoing a compression resistance test.

[0057] In the present invention, the particle crushing force can be obtained by testing using the Xiamen Yuanneng Technology Single Particle Mechanical Properties Test System (SPFT2000), and the specific test method is as follows: 0.5 g of graphite material is added to a beaker containing 20 mL of anhydrous ethanol, and ultrasonically dispersed for 5 minutes to obtain a dispersion; 100 μL of the above dispersion is added dropwise onto a glass slide, and the glass slide is transferred to the SPFT2000 sample observation platform; the single particle is positioned using the optical microscope of the SPFT2000, and the pressure head is controlled to press down at a uniform speed, and the stress mutation point during the particle compression process is recorded as the particle crushing force.

[0058] In a preferred embodiment, the carbon content of the first graphite material is greater than 99.9%, where the percentage is the mass percentage of the first graphite material.

[0059] In a preferred embodiment, the carbon content of the second graphite material is greater than 99.9%, where the percentage is the mass percentage of the first graphite material.

[0060] In a preferred embodiment, the Dv50 particle size of the first graphite material is 14-18 μm, for example, 16 μm.

[0061] In a preferred embodiment, the Dv50 particle size of the second graphite material is 9-13 μm, for example, 11 μm.

[0062] In a preferred embodiment, the first graphite material is a microcrystalline graphite material.

[0063] In a preferred embodiment, the second graphite material is a microcrystalline graphite material.

[0064] In a preferred embodiment, the content of the first binder is 1.3%-1.8%, for example, 1.5%, where the percentage is the mass percentage of the first active material layer.

[0065] In a preferred embodiment, the content of the second binder is 0.7%-1.2%, for example, 1.1%, where the percentage is the mass percentage of the second active material layer.

[0066] Among them, the types of the first binder and the second binder are not particularly limited, and can be independently selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid (PAA), ethylene-propylene-diene terpolymer and its sulfonate, styrene-butadiene rubber (SBR), fluororubber and various copolymers, such as SBR.

[0067] In a preferred embodiment, the content of the first graphite material is greater than 20%, preferably greater than 50%, for example, 96.2%, 96.5% or 96.7%, where the percentage is the mass percentage of the first active material layer.

[0068] In a preferred embodiment, the content of the second graphite material is greater than 20%, preferably greater than 50%, for example, 96.3%, 96.8% or 96.9%, where the percentage is the mass percentage of the second active material layer.

[0069] In a preferred embodiment, the mass ratio of the first active material layer to the second active material layer is 1:(0.4-2.5), for example, 1:0.43, 1:0.67, 1:1, 1:1.5 or 1:2.33.

[0070] In a preferred embodiment, the thickness of the first active material layer is 50-120 μm, for example, 55 μm.

[0071] In a preferred embodiment, the thickness of the second active material layer is 50-110 μm, for example, 55 μm.

[0072] In some embodiments, the first active material layer further includes a thickener, wherein the content of the thickener is, for example, 1.2%, where the percentage is the mass percentage of the first active material layer.

[0073] In some embodiments, the second active material layer further includes a thickener, wherein the content of the thickener is, for example, 1.2%, where the percentage is the mass percentage of the second active material layer.

[0074] The thickener may be a thickener conventionally used in the art for preparing negative electrode sheets, such as sodium carboxymethyl cellulose (CMC).

[0075] In some embodiments, the first active material layer further includes a conductive agent, wherein the content of the conductive agent is, for example, 0.8%, where the percentage is the mass percentage of the first active material layer.

[0076] In some embodiments, the second active material layer further includes a conductive agent, wherein the content of the conductive agent is, for example, 0.8%, where the percentage is the mass percentage of the second active material layer.

[0077] There are no particular restrictions on the conductive agent, as long as it has conductivity and does not cause chemical changes in the battery. For example, the conductive agent may be: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black (Super P), acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black or carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum or silver; conductive whiskers, such as zinc oxide whiskers or potassium titanate whiskers; conductive metal oxides, such as titanium dioxide; or conductive polymers, such as polyphenylene derivatives. The conductive agent is, for example, conductive carbon SP.

[0078] In some specific embodiments, in the first active material layer, the mass ratio of the first graphite material, the conductive agent, the first binder and the thickener is 96.5:0.8:1.5:1.2.

[0079] In some specific embodiments, in the first active material layer, the mass ratio of the first graphite material, the conductive agent, the first binder and the thickener is 96.7:0.8:1.3:1.2.

[0080] In some specific embodiments, in the first active material layer, the mass ratio of the first graphite material, the conductive agent, the first binder and the thickener is 96.2:0.8:1.8:1.2.

[0081] In some specific embodiments, in the second active material layer, the mass ratio of the second graphite material, the conductive agent, the second binder and the thickener is 96.9:0.8:1.1:1.2.

[0082] In some specific embodiments, in the second active material layer, the mass ratio of the second graphite material, the conductive agent, the second binder and the thickener is 96.3:0.8:0.7:1.2.

[0083] In some specific embodiments, in the second active material layer, the mass ratio of the second graphite material, the conductive agent, the second binder and the thickener is 96.8:0.8:1.2:1.2.

[0084] In the present invention, the negative electrode current collector may be a conventional negative electrode current collector in the art. The negative electrode current collector is used as a substrate to support the first active material layer and the second active material layer, and is generally a metal foil having a thickness of 3-500 microns. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system. For example, it can be a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, etc. The negative electrode current collector is generally a smooth surface, but fine lines may also be formed on its surface to increase the adhesion between the first active material layer and the current collector. In addition to the foil, the negative electrode current collector may also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. Generally, the negative electrode current collector is copper foil.

[0085] In a preferred embodiment, the method for preparing the negative electrode sheet comprises the following steps:

[0086] S1. applying a first negative electrode slurry layer on at least one surface of the negative electrode current collector, wherein the first negative electrode slurry layer comprises a first graphite material and a first binder;

[0087] S2, applying a second negative electrode slurry layer on the first negative electrode slurry layer, wherein the second negative electrode slurry layer comprises a second graphite material and a second binder;

[0088] S3, drying, cold pressing, and you are done.

[0089] In some more preferred embodiments, the coating density of the first negative electrode slurry layer is greater than 0.055 g / cm 2 , preferably greater than 0.14 g / cm 2 , for example 0.60 g / cm 2 .

[0090] In some more preferred embodiments, the coating density of the second negative electrode slurry layer is greater than 0.055 g / cm 2 , preferably greater than 0.14 g / cm 2 , for example 0.60 g / cm 2 .

[0091] In some more preferred embodiments, in step S1, the first graphite material is obtained by pre-treating a first graphite precursor, and the pre-treatment includes surface oxidation treatment and / or carboxylation treatment.

[0092] In some more preferred embodiments, in step S2, the second graphite material is obtained by pre-treating a second graphite precursor, and the pre-treatment includes surface oxidation treatment and / or carboxylation treatment.

[0093] In some preferred embodiments, the first graphite precursor may be microcrystalline graphite.

[0094] In some preferred embodiments, the second graphite precursor may be microcrystalline graphite.

[0095] Microcrystalline graphite

[0096] In the present invention, the microcrystalline graphite preferably satisfies the following conditions: La≤72 nm, Lc≤15 nm; wherein La is the lattice constant of the graphite crystal in the microcrystalline graphite at the 110 plane, and Lc is the lattice constant of the graphite crystal in the microcrystalline graphite at the 002 plane; F p ≥15 mN, F p is the particle crushing force.

[0097] In some preferred embodiments, La≤60 nm.

[0098] In some specific embodiments, the first graphite precursor is microcrystalline graphite, and the La is, for example, 68 nm, 70 nm, 71 nm or 72 nm.

[0099] In some specific embodiments, the second graphite precursor is microcrystalline graphite, and the La is, for example, 66 nm, 68 nm, 69 nm, or 70 nm.

[0100] In some preferred embodiments, Lc ≤ 12 nm.

[0101] In some specific embodiments, the first graphite precursor is microcrystalline graphite, and the Lc is, for example, 13 nm, 14 nm, or 15 nm.

[0102] In some specific embodiments, the second graphite precursor is microcrystalline graphite, and the Lc is, for example, 12 nm, 13 nm, or 14 nm.

[0103] In some preferred embodiments, 15 mN≤F p ≤25 mN.

[0104] In some specific embodiments, the first graphite precursor is microcrystalline graphite, and the F pFor example, 23 mN or 25 mN.

[0105] In some specific embodiments, the second graphite precursor is microcrystalline graphite, and the F p For example, 20 mN or 21 mN.

[0106] In some preferred embodiments, the particle size distribution symmetry of the microcrystalline graphite satisfies 0<S≤0.1, preferably 0<S≤0.07.

[0107] In some specific embodiments, the first graphite precursor is microcrystalline graphite, and the particle size distribution symmetry is, for example, 0.012, 0.023, 0.035 or 0.038.

[0108] In some specific embodiments, the second graphite precursor is microcrystalline graphite, and the particle size distribution symmetry is, for example, 0.028, 0.032, 0.046, or 0.052.

[0109] In some preferred embodiments, the sphericity of the microcrystalline graphite is preferably 0.5-1.0.

[0110] In some specific embodiments, the first graphite precursor is microcrystalline graphite, and the sphericity of the microcrystalline graphite is, for example, 0.90 or 0.91.

[0111] In some specific embodiments, the second graphite precursor is microcrystalline graphite, and the sphericity of the microcrystalline graphite is, for example, 0.88 or 0.89.

[0112] In some preferred embodiments, the carbon content of the microcrystalline graphite is greater than 99.9%, where the percentage is the mass percentage of the microcrystalline graphite.

[0113] In a preferred embodiment, the Dv50 particle size of the first graphite precursor is 14-18 μm, for example, 16 μm.

[0114] In a preferred embodiment, the Dv50 particle size of the second graphite precursor is 9-13 μm, for example, 11 μm.

[0115] Wherein, La is Calculated. is 0.0027 nm, is the half-peak width, θ is based on Calculated; among them, The specific test method of d(110) is as follows: add the graphite material and 50 mL of n-hexane into a beaker, perform ultrasonic oscillation for 5 min, then use a pipette to draw 100 μL of the solution and drop it onto the TEM observation copper grid, quickly dry the copper grid and observe it; use TEM to select diffraction observation and calibration to obtain and d(110).

[0116] Wherein, Lc is given by Calculated. is 0.0027 nm, is the half-peak width, θ' is based on Calculated; among them, The specific test method of d(002) is as follows: add the graphite material and 50 mL of n-hexane into a beaker, perform ultrasonic oscillation for 5 min, then use a pipette to draw 100 μL of the solution and drop it onto the TEM observation copper grid, quickly dry the copper grid and observe it; use TEM to select diffraction observation and calibration to obtain and d(002).

[0117] Wherein, the particle crushing force (F p ) refers to the critical pressure at which a single particle of a material breaks when subjected to a compression test. The particle crushing force can be obtained by using the Xiamen Yuanneng Technology Single Particle Mechanical Properties Test System (SPFT2000). The specific test method is as follows: add 0.5g of graphite material to a beaker containing 20ml of anhydrous ethanol, and ultrasonically disperse for 5 minutes to obtain a dispersion; take 100μL of the above dispersion and drop it onto a glass slide, and transfer the glass slide to the SPFT2000 sample observation platform; use the optical microscope of the SPFT2000 to locate the single particle, control the pressure head to press down at a uniform speed, and record the stress mutation point during the particle compression process as the particle crushing force.

[0118] The particle size distribution symmetry (S) is calculated by [D (3,4) - Dv50] / Dv50; wherein D (3,4) and Dv50 are tested according to GB / T 41949-2022. The smaller the particle size distribution symmetry, the better the particle size distribution symmetry, and the higher the peak of the differential curve of the particle size distribution.

[0119] The sphericity (D) refers to the ratio of the surface area of ​​a sphere with the same volume as the material particle to the surface area of ​​the material particle. Generally speaking, the closer the particle is to a sphere in appearance, the closer its sphericity is to 1. The sphericity of a sphere is equal to 1, and the sphericity of other objects is less than 1. The sphericity is tested in accordance with GB / T 37406-2019.

[0120] In some specific embodiments, the method for preparing microcrystalline graphite comprises the following steps:

[0121] ① A microcrystalline graphite precursor and a binder are first mixed, and a solvent is added to perform a second mixing to obtain a mixture; wherein the temperature of the first mixing is 5-20° C. below the softening point of the binder;

[0122] ② Pressing the mixture to obtain a microcrystalline graphite blank;

[0123] ③ laying the microcrystalline graphite rough blank on the surface of the graphitization furnace, laying the graphitized thermal insulation material on the microcrystalline graphite rough blank, and performing graphitization treatment. The microcrystalline graphite rough blank is subjected to graphitization treatment to obtain a microcrystalline graphite embryo body;

[0124] ④ The microcrystalline graphite embryo is crushed.

[0125] Optionally, the first mixing temperature is 8-15°C below the softening point of the binder, for example, 10°C.

[0126] Wherein, optionally, in step ①, the fixed carbon content of the microcrystalline graphite precursor is 88%-91%.

[0127] Wherein, optionally, in step ①, the Dv50 particle size of the microcrystalline graphite precursor is 6-8 μm, for example, 7 μm.

[0128] Wherein, optionally, in step ①, the mass ratio of the microcrystalline graphite precursor to the binder is (2-7):1, preferably (4-7):1, for example, 5:2.

[0129] Wherein, optionally, in step ①, the binder includes one or more of petroleum asphalt, phenolic resin, epoxy resin and coal tar.

[0130] Wherein, optionally, in step ①, the softening point of the binder is 100-250°C, preferably 100-130°C, for example 110°C.

[0131] Wherein, optionally, in step ①, the solvent is selected from one or more of xylene, toluene and n-hexane.

[0132] Wherein, optionally, in step ①, the solid content of the mixture is 40%-60%, for example, 45%, where the percentage is the mass percentage of the solid component of the mixture to the mass percentage of the mixture.

[0133] Wherein, optionally, in step ①, the first mixing method is stirring; wherein the stirring time is preferably 0.5-2h, for example 1h; and the stirring speed is preferably 30-90r / min.

[0134] Wherein, optionally, in step ①, the second mixing method is stirring; wherein the stirring time is preferably 0.5-2h, for example 1h; the stirring speed is preferably 60-120r / min; and the stirring temperature is preferably room temperature.

[0135] Wherein, optionally, in step ①, the method for preparing the microcrystalline graphite precursor includes the following steps: washing and flotation of the microcrystalline graphite ore, and then coarse crushing and spheroidization to obtain a graphite precursor; wherein the spheroidization time is preferably 4-24h; and the spheroidization is preferably carried out using a honeycomb mill.

[0136] Wherein, optionally, in step ②, the pressing is isostatic pressing; wherein the time of the isostatic pressing is preferably 18-30 hours, for example, 24 hours; the pressure of the isostatic pressing is preferably 150-300 MPa, for example, 200 MPa.

[0137] Wherein, optionally, in step ③, the temperature of the graphitization treatment is greater than 1600°C.

[0138] Wherein, optionally, in step ③, the graphitization treatment time is 18-40h, preferably 24-36h.

[0139] Wherein, optionally, in step ③, the graphitized thermal insulation material is petroleum coke and / or asphalt coke.

[0140] Wherein, optionally, in step ③, the graphitization equipment is a graphitization furnace.

[0141] Wherein, optionally, in step ④, the pulverizing process further includes screening and magnetic impurity removal.

[0142] Electrochemical Devices

[0143] In the electrochemical device provided in the second aspect of the present invention, it comprises the negative electrode sheet as described above.

[0144] In the present invention, the electrochemical device is preferably a battery.

[0145] In an optional embodiment, the electrochemical device is a lithium ion battery; the lithium ion battery comprises the negative electrode sheet, the positive electrode sheet, a separator and an electrolyte.

[0146] Positive electrode

[0147] In the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.

[0148] In the present invention, the positive electrode active material in the positive electrode active material layer may be a positive electrode active material conventionally used in the art, such as one or more of lithium nickel cobalt manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, lithium manganese iron phosphate and lithium cobalt oxide.

[0149] In some optional embodiments, the positive electrode active material layer further includes a binder.

[0150] The type of the binder is not particularly limited, and can be selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid (PAA), ethylene-propylene-diene terpolymer and its sulfonate, styrene-butadiene rubber (SBR), fluororubber and various copolymers, such as PVDF.

[0151] In some optional embodiments, the content of the binder is 1%-10%, for example, 1.8%, where the percentage is the mass percentage of the positive electrode active material layer.

[0152] In some optional embodiments, the positive electrode active material layer further includes a conductive agent.

[0153] The type of the conductive agent is not particularly limited, and is a reagent used to ensure that the electrode has good charge and discharge performance. It can be selected from graphite materials such as natural graphite and artificial graphite, carbon black SP, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and other carbon black materials, carbon fibers, metal fibers and other conductive fibers, metal powders such as carbon fluoride powder, aluminum powder, nickel powder and other metal powders, zinc oxide, potassium titanate and other conductive whiskers, and titanium dioxide and other conductive metal oxides or polyphenylene derivatives.

[0154] In a specific embodiment, the conductive agent is conductive carbon SP.

[0155] In some optional embodiments, the content of the conductive agent is 0.2%-3%, for example, 1.2%, where the percentage is the mass percentage of the positive electrode active material layer.

[0156] In some specific embodiments, in the positive electrode active material layer, the mass ratio of the positive electrode active material, the conductive agent and the binder is 97:1.2:1.8.

[0157] In the present invention, the positive electrode current collector may be a conventional positive electrode current collector in the art. The positive electrode current collector is used as a substrate to support the positive electrode active material layer, and is generally a metal foil having a thickness of 3-500 microns. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system. For example, it can be a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, etc. The positive electrode current collector is generally a smooth surface, but fine lines may also be formed on its surface to increase the adhesion between the positive electrode active material layer and the current collector. In addition to the foil, the positive electrode current collector may also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. Generally, the positive electrode current collector is aluminum foil.

[0158] In some embodiments, the preparation method of the positive electrode sheet includes: fully stirring and mixing the components of the positive electrode active material layer in a solvent to obtain a positive electrode slurry, coating it on at least one surface of the positive electrode collector, drying it, and rolling and compacting it.

[0159] In some optional embodiments, the solvent includes one or more of N-methylpyrrolidone (NMP), dimethyl carbonate, ethylene carbonate and diethylene carbonate, for example, NMP.

[0160] Diaphragm

[0161] In the present invention, the separator in the battery cell may be a separator conventionally used in the art.

[0162] In some optional embodiments, the separator may be made of polypropylene film or polyethylene film.

[0163] Wherein, the air permeability of the diaphragm may be 180-380 s / 100mL.

[0164] Wherein, the porosity of the diaphragm may be 30%-50%.

[0165] Wherein, the thickness of the diaphragm may be 9-18 μm.

[0166] In a specific embodiment, the diaphragm is a polyethylene film; the thickness of the diaphragm is 11 μm; the air permeability of the diaphragm is 230 s / 100 mL; and the porosity of the diaphragm is 40%.

[0167] Electrolyte

[0168] In some embodiments, the electrolyte may be an electrolyte conventionally used for batteries in the art, generally including a non-aqueous solvent, a lithium salt, and additives.

[0169] In some embodiments, the preparation method of the lithium-ion battery includes the following steps: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, so that the separator is located between the positive and negative electrode sheets to play an isolating role; then wrapping with an aluminum-plastic film, injecting the electrolyte after drying, and finally preparing a soft-pack battery through packaging, standing, formation and other processes.

[0170] Electronic devices

[0171] The electronic device provided in the third aspect of the present invention comprises the electrochemical device as described above.

[0172] Exemplarily, the electronic device described in the present invention may be, but is not limited to, mobile devices (such as mobile phones, tablet computers, laptop computers, video recorders, portable printers / copiers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems and backup power supplies, etc.

[0173] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0174] The reagents and raw materials used in the present invention are commercially available.

[0175] Example 1

[0176] 1. Preparation of the first graphite material and the second graphite material

[0177] (1) Preparing a first graphite precursor and a second graphite precursor:

[0178] ① The microcrystalline graphite ore (purchased from Lutang Graphite Processing Plant in Chenzhou, Hunan Province, model is first-class earthy graphite, the carbon content of the original ore is >85%) is subjected to preliminary water washing and flotation to make its fixed carbon content reach 90%, and after coarse crushing, it is spheroidized by using a honeycomb mill for 6 hours to obtain a microcrystalline graphite precursor with a sphericity of 0.83 (Dv50 particle size is 7μm); the above-mentioned microcrystalline graphite precursor is mixed with petroleum asphalt with a softening point of 110°C (purchased from Liaoning Xinde New Materials Technology Co., Ltd., model XD-110) at a mixing mass ratio of 5:2, heated to 10°C below the softening point (100°C) and stirred for 1h (stirring speed is 15r / min-20r / min), and then an appropriate amount of xylene solvent is added to assist the dispersion of the petroleum asphalt, and stirring is continued for 1h to obtain a mixture (solid content is 45%);

[0179] ② Then, the mixture is added into a 40×30cm×30cm rubber mold, and isostatically pressed at 200MPa for 24h, and then demolded to obtain a microcrystalline graphite rough embryo;

[0180] ③ The above-mentioned microcrystalline graphite rough embryo is spread on the surface of the Acheson graphitization furnace as a graphitization insulation material, and then a layer of petroleum coke is spread and graphitized. The graphitization temperature is 3000°C and the graphitization time is 36h; wherein the microcrystalline graphite rough embryo forms a microcrystalline graphite embryo body.

[0181] ④ Take out the above-mentioned microcrystalline graphite embryo and crush it, first filter it with a 250-mesh screen, and then screen it with a 325-mesh screen after shaping. The unscreened material is recorded as material A, and the screened material is recorded as material B;

[0182] Material A was crushed, shaped, sieved and magnetically impurized to control the Dv50 particle size to 16 μm, and the first graphite precursor (carbon content of 99.9%, La of 70 nm, Lc of 14 nm, particle crushing force F p is 23 mN, the particle size distribution symmetry S is 0.023, and the sphericity D is 0.90);

[0183] Material B was crushed, shaped, sieved and magnetically impurized to control the Dv50 particle size to 11 μm to obtain the second graphite precursor (carbon content of 99.9%, La of 68 nm, Lc of 13 nm, particle crushing force F p is 20 mN, the particle size distribution symmetry S is 0.032, and the sphericity D is 0.88).

[0184] (2) The first graphite precursor and the second graphite precursor obtained above are subjected to surface oxidation treatment and carboxylation treatment respectively, and the specific steps are as follows:

[0185] S0-1, surface oxidation treatment: placing the first graphite precursor in a rotary kiln, passing air at a temperature of 800° C. for surface oxidation treatment for 1 hour; in addition, placing the second graphite precursor in a rotary kiln, passing air at a temperature of 800° C. for surface oxidation treatment for 20 minutes;

[0186] S0-2, carboxylation treatment:

[0187] Prepare 20L of chloroacetic acid solution with a concentration of 5 mol / L, then add 3kg of the first graphite precursor subjected to surface oxidation treatment, heat to 60°C and stir for 8h, collect the powder after filtration, then heat to 240°C at 2°C / min under vacuum, and then keep warm for 2h to obtain a first graphite material (Dv50 particle size of 16μm, carbon content of 99.9%);

[0188] Prepare 20L of 2 mol / L chloroacetic acid solution, then add 3kg of the second graphite precursor treated with surface oxidation, heat to 60°C and stir for 8h, collect the above powder after filtration, then heat to 240°C at 2°C / min under vacuum, and then keep warm for 2h to obtain a second graphite material (Dv50 particle size is 11μm, carbon content is 99.9%).

[0189] 2. Preparation of negative electrode sheet

[0190] S1. The obtained first graphite material, conductive agent (conductive carbon SP), first binder SBR and thickener CMC were mixed in a mass ratio of 96.5:0.8:1.5:1.2 (a total of 100 parts by mass), and 82 parts by mass of deionized water were added and mixed evenly to obtain a first negative electrode slurry; the first negative electrode slurry was coated on a copper foil to form a first negative electrode slurry layer (coating density was 0.60 g / cm 2 );

[0191] S2. The obtained second graphite material, conductive agent (conductive carbon SP), second binder SBR and thickener CMC were mixed in a mass ratio of 96.9:0.8:1.1:1.2 (a total of 100 parts by mass), and 82 parts by mass of deionized water were added and mixed evenly to obtain a second negative electrode slurry; the second negative electrode slurry was then coated on the first negative electrode slurry layer to form a second negative electrode slurry layer (coating density was 0.60 g / cm 2 );

[0192] S3. After drying, cold pressing is performed once to form a first compaction, and then cold pressing is performed twice to form a second compaction to obtain a negative electrode sheet; wherein the first negative electrode slurry layer forms a first active material layer, the second negative electrode slurry layer forms a second active material layer, the mass ratio of the first active material layer to the second active material layer is 5:5, and the thickness of the first active material layer and the second active material layer are both 55 μm.

[0193] 3. Preparation of lithium-ion batteries

[0194] The positive electrode sheet, the separator and the negative electrode sheet are wound to obtain a battery cell, which is then packaged in a packaging shell and injected with electrolyte to obtain a soft-pack battery.

[0195] Among them, the preparation of the positive electrode sheet includes the following steps: mixing the positive electrode active material NCM622, PVDF and conductive carbon SP in a mass ratio of 97:1.8:1.2 (a total of 100 parts by mass), adding 82 parts by mass of NMP to obtain a positive electrode slurry; coating the obtained positive electrode slurry on at least one surface of an aluminum foil, drying, and rolling and compacting.

[0196] Among them, the diaphragm is a polyethylene film; the thickness of the diaphragm is 11 μm; the air permeability of the diaphragm is 230 s / 100 mL; and the porosity of the diaphragm is 40%.

[0197] Among them, the electrolyte used is commercial electrolyte (the manufacturer is Xinya Shanshan New Materials Technology (Quzhou) Co., Ltd., model E3).

[0198] Example 2

[0199] The only difference between Example 2 and Example 1 is that in the preparation of the first graphite material and the second graphite material, in step S0-1, the temperature of the surface oxidation treatment is 600°C, and the other conditions are the same as those in Example 1.

[0200] Example 3

[0201] The only difference between Example 3 and Example 1 is that in the preparation of the first graphite material and the second graphite material, in step S0-1, the temperature of the surface oxidation treatment is 1000°C, and the other conditions are the same as those in Example 1.

[0202] Example 4

[0203] The only difference between Example 4 and Example 1 is that in the preparation of the first graphite material and the second graphite material, in step S0-1, the time for the surface oxidation treatment of the first graphite precursor is 0.5 h, and the other conditions are the same as those in Example 1.

[0204] Example 5

[0205] The only difference between Example 5 and Example 1 is that in the preparation of the first graphite material and the second graphite material, in step S0-1, the time for the surface oxidation treatment of the second graphite precursor is 30 minutes, and the other conditions are the same as those in Example 1.

[0206] Example 6

[0207] The only difference between Example 6 and Example 1 is that in the preparation of the first graphite material and the second graphite material, in step S0-1, the time for the surface oxidation treatment of the second graphite precursor is 10 minutes, and the other conditions are the same as those in Example 1.

[0208] Example 7

[0209] The only difference between Example 7 and Example 1 is that in the preparation of the first graphite material and the second graphite material, in step S0-2, the concentration of chloroacetic acid is 4 mol / L, and the other conditions are the same as those in Example 1.

[0210] Example 8

[0211] The only difference between Example 8 and Example 1 is that in the preparation of the first graphite material and the second graphite material, in step S0-3, the concentration of chloroacetic acid is 3 mol / L, and the other conditions are the same as those in Example 1.

[0212] Example 9

[0213] The only difference between Example 9 and Example 1 is that in the preparation of the first graphite material and the second graphite material, in step S0-3, the concentration of chloroacetic acid is 1.5 mol / L, and the other conditions are the same as those in Example 1.

[0214] Example 10

[0215] The only difference between Example 10 and Example 1 is that in the preparation of the negative electrode sheet, in step S1, the mass ratio of the first graphite material, the conductive agent, the first binder and the thickener is 96.7:0.8:1.3:1.2, and the other conditions are the same as those in Example 1.

[0216] Embodiment 11

[0217] The only difference between Example 11 and Example 1 is that in the preparation of the negative electrode sheet, in step S1, the mass ratio of the first graphite material, the conductive agent, the first binder and the thickener is 96.2:0.8:1.8:1.2, and the other conditions are the same as those in Example 1.

[0218] Example 12

[0219] The only difference between Example 12 and Example 1 is that in the preparation of the negative electrode sheet, in step S2, the mass ratio of the second graphite material, the conductive agent, the second binder and the thickener is 96.3:0.8:0.7:1.2, and the other conditions are the same as in Example 1.

[0220] Example 13

[0221] The only difference between Example 13 and Example 1 is that in the preparation of the negative electrode sheet, in step S2, the mass ratio of the second graphite material, the conductive agent, the second binder and the thickener is 96.8:0.8:1.2:1.2, and the other conditions are the same as those in Example 1.

[0222] Embodiment 14

[0223] The only difference between Example 14 and Example 1 is that in the preparation of the negative electrode sheet, in step S3, the mass ratio of the first active material layer to the second active material layer is 3:7, and the other conditions are the same as those in Example 1.

[0224] Embodiment 15

[0225] The only difference between Example 15 and Example 1 is that in the preparation of the negative electrode sheet, in step S3, the mass ratio of the first active material layer to the second active material layer is 4:6, and the other conditions are the same as those in Example 1.

[0226] Example 16

[0227] The only difference between Example 16 and Example 1 is that in the preparation of the negative electrode sheet, in step S3, the mass ratio of the first active material layer to the second active material layer is 6:4, and the other conditions are the same as those in Example 1.

[0228] Embodiment 17

[0229] The only difference between Example 17 and Example 1 is that in the preparation of the negative electrode sheet, in step S3, the mass ratio of the first active material layer to the second active material layer is 7:3, and the other conditions are the same as those in Example 1.

[0230] Embodiment 18

[0231] The difference between Example 18 and Example 1 is that in the preparation of the first graphite precursor and the second graphite precursor, in step ④, material A is crushed, shaped, sieved and magnetically impurized, and the Dv50 particle size is controlled to be 18 μm to obtain the first graphite precursor (carbon content is 99.9%, La is 71 nm, Lc is 15 nm, and particle crushing force F is 1.375 μm). p The particle size distribution symmetry S is 0.012, and the sphericity D is 0.91). The other conditions are the same as those in Example 1.

[0232] Embodiment 19

[0233] The difference between Example 19 and Example 1 is that in the preparation of the first graphite precursor and the second graphite precursor, in step ④, material B is crushed, shaped, sieved and magnetically impurized, and the Dv50 particle size is controlled to be 13 μm to obtain a second graphite precursor (carbon content of 99.9%, La of 69 nm, Lc of 14 nm, particle crushing force F p The particle size distribution symmetry S is 0.028, and the sphericity D is 0.89). The other conditions are the same as those in Example 1.

[0234] Embodiment 20

[0235] The difference between Example 20 and Example 1 is that when preparing the first graphite precursor and the second graphite precursor, the mixture is heated to 5°C below the softening point (105°C) and stirred for 1 hour in step ①. The other conditions are the same as those in Example 1.

[0236] The carbon content of the first graphite precursor obtained is 99.9%, La is 68 nm, Lc is 13 nm, and the particle crushing force F p is 23 mN, the particle size distribution symmetry S is 0.035, and the sphericity D is 0.90;

[0237] The carbon content of the obtained second graphite precursor is 99.9%, La is 66 nm, Lc is 12 nm, and the particle crushing force F pis 20 mN, the particle size distribution symmetry S is 0.046, and the sphericity D is 0.88.

[0238] Embodiment 21

[0239] The difference between Example 21 and Example 1 is that when preparing the first graphite precursor and the second graphite precursor, the mixture is heated to 20° C. (90° C.) below the softening point and stirred for 1 hour in step ①. The other conditions are the same as those in Example 1.

[0240] The carbon content of the first graphite precursor obtained is La is 72 nm, Lc is 15 nm, and the particle crushing force F p is 23 mN, the particle size distribution symmetry S is 0.038, and the sphericity D is 0.90;

[0241] The carbon content of the obtained second graphite precursor is 99.9%, La is 70 nm, Lc is 13 nm, and the particle crushing force F p is 20 mN, the particle size distribution symmetry S is 0.052, and the sphericity D is 0.88.

[0242] Comparative Example 1

[0243] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, in step S0-1, the temperature of the surface oxidation treatment is 500° C., and the other conditions are the same as those in Example 1.

[0244] Comparative Example 2

[0245] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, in step S0-1, the temperature of the surface oxidation treatment is 1100° C., and the other conditions are the same as those in Example 1.

[0246] Comparative Example 3

[0247] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, in step S0-1, the time for the surface oxidation treatment of the first graphite precursor is 0.2 h, and the other conditions are the same as those in Example 1.

[0248] Comparative Example 4

[0249] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, in step S0-1, the time for the surface oxidation treatment of the second graphite precursor is 5 minutes, and the other conditions are the same as those in Example 1.

[0250] Comparative Example 5

[0251] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, in step S0-1, the time for the surface oxidation treatment of the second graphite precursor is 40 minutes, and the other conditions are the same as those in Example 1.

[0252] Comparative Example 6

[0253] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, in step S0-1, the second graphite precursor is not subjected to surface oxidation treatment, and the other conditions are the same as those in Example 1.

[0254] Comparative Example 7

[0255] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, in step S0-2, the concentration of chloroacetic acid is 2 mol / L, and the other conditions are the same as those in Example 1.

[0256] Comparative Example 8

[0257] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, in step S0-3, the concentration of chloroacetic acid is 5 mol / L, and the other conditions are the same as those in Example 1.

[0258] Comparative Example 9

[0259] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, in step S0-3, the concentration of chloroacetic acid is 1 mol / L, and the other conditions are the same as those in Example 1.

[0260] Comparative Example 10

[0261] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, in step S1, the mass ratio of the first graphite material, the conductive agent, the first binder and the thickener is 96.0:0.8:2.0:1.2, and the other conditions are the same as those in Example 1.

[0262] Comparative Example 11

[0263] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, in step S1, the mass ratio of the first graphite material, the conductive agent, the first binder and the thickener is 96.9:0.8:1.1:1.2, and the other conditions are the same as those in Example 1.

[0264] Comparative Example 12

[0265] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, in step S2, the mass ratio of the second graphite material, the conductive agent, the second binder and the thickener is 96.7:0.8:1.3:1.2, and the other conditions are the same as those in Example 1.

[0266] Comparative Example 13

[0267] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, in step S2, the mass ratio of the second graphite material, the conductive agent, the second binder and the thickener is 97.5:0.8:0.5:1.2, and the other conditions are the same as those in Example 1.

[0268] Comparative Example 14

[0269] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, only the second negative electrode slurry is coated on the negative electrode current collector to obtain the second active material layer (thickness of 110 μm), without the first active material layer. The other conditions are the same as those in Example 1.

[0270] Comparative Example 15

[0271] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, only the first negative electrode slurry is coated on the negative electrode current collector to obtain the first active material layer (thickness of 110 μm), and there is no second active material layer. The other conditions are the same as those in Example 1.

[0272] Comparative Example 16

[0273] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, step S1 and step S2 are replaced by the following steps:

[0274] S1. The obtained second graphite material, conductive agent (conductive carbon SP), second binder SBR and thickener CMC were mixed in a mass ratio of 96.9:0.8:1.1:1.2 (a total of 100 parts by mass), and 82 parts by mass of deionized water were added and mixed evenly to obtain a second negative electrode slurry; the second negative electrode slurry was then coated on a copper foil to form a second negative electrode slurry layer (coating density was 0.60 g / cm 2 );

[0275] S2. The obtained first graphite material, conductive agent (conductive carbon SP), first binder SBR and thickener CMC are mixed in a mass ratio of 96.5:0.8:1.5:1.2 (a total of 100 parts by mass), and 82 parts by mass of deionized water are added and mixed evenly to obtain a first negative electrode slurry; the first negative electrode slurry is coated on the second negative electrode slurry layer to form a first negative electrode slurry layer (coating density is 0.60 g / cm 2 ).

[0276] The remaining conditions are the same as those in Example 1.

[0277] Comparative Example 17

[0278] The difference between this comparative example and Example 1 is that the preparation of the negative electrode sheet is replaced by the following steps:

[0279] S1, mixing the obtained first graphite material, conductive agent (conductive carbon SP), first binder SBR and thickener CMC in a mass ratio of 96.5:0.8:1.5:1.2 (a total of 100 parts by mass), adding 82 parts by mass of deionized water and mixing evenly to obtain a first negative electrode slurry;

[0280] S2, mixing the obtained second graphite material, conductive agent (conductive carbon SP), second binder SBR and thickener CMC in a mass ratio of 96.9:0.8:1.1:1.2 (a total of 100 parts by mass), adding 82 parts by mass of deionized water and mixing evenly to obtain a second negative electrode slurry;

[0281] The first negative electrode slurry and the second negative electrode slurry were mixed and coated on the copper foil to form a negative electrode slurry layer (coating density was 0.60 g / cm 2 );

[0282] S3, drying, and then cold pressing once to obtain a negative electrode sheet under a first compression, and then cold pressing twice to obtain a negative electrode sheet under a second compression; wherein the negative electrode slurry layer forms an active material layer with a thickness of 110 μm.

[0283] The remaining conditions are the same as those in Example 1.

[0284] Comparative Example 18

[0285] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, a commercial graphite material (purchased from Shanghai Shanshan Technology Co., Ltd., model FSN-1) is used as the negative electrode material. The specific preparation process is as follows:

[0286] Graphite material, conductive agent (conductive carbon SP), binder SBR and thickener CMC were mixed in a mass ratio of 96.5:0.8:1.5:1.2 (a total of 100 parts by mass), and 82 parts by mass of deionized water were added and mixed evenly to obtain a negative electrode slurry; the negative electrode slurry was coated on a copper foil to form a negative electrode slurry layer (coating density was 0.60 g / cm 2 );

[0287] The negative electrode sheet was dried, and then cold pressed once to obtain a negative electrode sheet under the first compression, and then cold pressed twice to obtain a negative electrode sheet under the second compression; wherein the negative electrode slurry layer formed an active material layer with a thickness of 110 μm.

[0288] The remaining conditions are the same as those in Example 1.

[0289] Comparative Example 19

[0290] The difference between this comparative example and Example 1 is that in the preparation of the negative electrode sheet, commercial microcrystalline graphite (particle size of 6.7 μm, particle crushing force of 14 mN, purchased from Shenzhen BTR New Energy Materials Co., Ltd., model number WJ-1) is used to replace the first graphite material and the second graphite material, and the other conditions are the same as those in Example 1.

[0291] Some parameters of Examples 1-21 and Comparative Examples 1-19 are shown in Table 1.

[0292] Effect Example 1

[0293] The first graphite precursor and the second graphite precursor in Examples 1, 18-19 and 20-21 were tested for lattice constants La, Lc, particle crushing force, particle size distribution symmetry S and sphericity D, and the first graphite material and the second graphite material in Examples 1-21 and Comparative Examples 1-19 were tested for particle crushing force. The specific test method is as follows:

[0294] (1) Lattice constants La and Lc:

[0295] The obtained sample to be tested was used as the test sample. The sample to be tested and 50 mL of n-hexane were added to a beaker and ultrasonically oscillated for 5 minutes. Then, 100 μL of the solution was drawn with a pipette and dropped onto the TEM observation copper grid. The copper grid was quickly dried and then observed.

[0296] The d(110) and half-peak width of the sample were obtained by TEM selected diffraction observation and calibration. , then according to ,in is 0.0027 nm, and θ can be obtained by calculation; then ;

[0297] The d(002) and half-peak width of the sample were obtained by TEM selected diffraction observation and calibration. , then according to ,in is 0.0027 nm, and θ' can be obtained by calculation. .

[0298] (2) Particle size distribution symmetry S

[0299] With reference to GB / T 41949-2022, the graphite material was tested using a laser particle size diffractometer (Malvern 3000). The D(3,4) and Dv50 particle size data were directly read from the test results, and S was obtained by calculation according to S=[D(3,4)-Dv50] / Dv50.

[0300] (3) Sphericity D

[0301] The sphericity is tested in accordance with GB / T 37406-2019.

[0302] (4) Particle crushing force

[0303] The particle crushing force test was carried out using the Xiamen Yuanneng Technology single particle mechanical properties test system (SPFT2000), as follows:

[0304] 0.5 g of the sample powder to be tested was added into a beaker containing 20 ml of anhydrous ethanol and ultrasonically dispersed for 5 min to obtain a dispersion. 100 μL of the dispersion was dripped onto a glass slide and the glass slide was transferred to the SPFT2000 sample observation platform. The single particle was positioned using the optical microscope of the SPFT2000 and the pressure head was controlled to press down at a uniform speed. The stress mutation point during the particle compression process was recorded as the particle crushing force.

[0305] Some test results are shown in Table 1.

[0306] Effect Example 2

[0307] The negative electrode sheets in Examples 1-21 and Comparative Examples 1-19 were tested for the relative decrease rate, electrode porosity, and electrode bonding strength F N And the ultimate compression test, the specific test method is as follows:

[0308] (1) Limit compression of negative electrode

[0309] When the appearance of the negative electrode sheet remains good, the negative electrode sheet is rolled by a roller press. When the thickness of the negative electrode sheet does not decrease when the roller press increases the pressure, the thickness of the negative electrode sheet after rolling is measured with a micrometer, and the thickness d is recorded. Then, the negative electrode sheet per unit area is intercepted, and the mass of the copper foil contained therein is subtracted, and the mass is recorded as w. The limit compaction of the negative electrode sheet is P = w / d. The limit compaction of the negative electrode sheet is an indicator to measure the energy density of the negative electrode sheet. The limit compaction of the negative electrode sheets of each embodiment and comparative example is shown in Table 1.

[0310] (2) Specific surface decrease rate of negative electrode

[0311] The negative electrode sheet was cut into 2cm×2cm negative electrode sheets, and the specific surface areas of the negative electrode sheets under the first compression and the second compression were tested respectively according to the national standard GB / T 19587-2017; the ratio of the specific surface area of ​​the electrode sheet under the second compression to that under the first compression is P, and the electrode sheet specific surface decrease rate P0=1-P.

[0312] The first compaction and the second compaction of each embodiment and comparative example are shown in Table 1.

[0313] (3) Porosity of the negative electrode

[0314] The first step is to obtain the negative electrode sheet under the second compression, in the same manner as the negative electrode sheet obtained in the above-mentioned test of the specific surface decrease rate of the negative electrode sheet.

[0315] The second step is to test according to the national standard GB21650.1-2008, and the porosity can be read directly.

[0316] (4) Adhesion force F of negative electrode N

[0317] Cut the negative electrode sheet to be tested into long strips (length × width = 10cm × 3cm), and bond it to a long quartz glass plate with VHB tape (slightly larger in area than the negative electrode sheet). Use a special small round roller to repeatedly roll the negative electrode sheet three times to ensure that the negative electrode sheet is fully bonded to the VHB. Use a universal stretching machine and select the standard method of measuring adhesion at 180° to test the adhesion of the negative electrode sheet. Test each sample three times and take the average value.

[0318] The specific test results are shown in Table 1.

[0319] Effect Example 3

[0320] The lithium ion batteries prepared in Examples 1-21 and Comparative Examples 1-19 were tested for discharge capacity, initial efficiency, fast charge time, number of cycles, and storage days. The specific test methods are as follows:

[0321] (1) Discharge capacity

[0322] At 25°C, the battery was first charged and discharged for one cycle at 0.1C in the working voltage range of 2.7V (discharge cut-off voltage) to 4.3V (charge cut-off voltage) to activate the battery. Then, the lithium-ion battery prepared above was connected to the Blue Electric charge and discharge tester, and it was charged and discharged for a long cycle to measure its charge capacity and discharge capacity. The working voltage range of the battery test was 2.7V (discharge cut-off voltage) to 4.3V (charge cut-off voltage), and the test rate was 0.3C.

[0323] First efficiency = discharge capacity / charge capacity × 100%.

[0324] (2) Fast charging time

[0325] The battery cell is directly charged to 8% SOC with a current of 0.33C, and then according to the actual measured three-electrode window test of the battery cell, the charging windows of 10%, 20%, 30%, 40%, 50%, 60%, 70% and 80% are C1, C2, C3, C4, C5, C6, C7 and C8 respectively. It is charged gradually to 80%, that is, 8%-10% is charged with C1, 10% to 20% is charged with C2, and so on. The charging time from 8% to 80% SOC is recorded as the measure of fast charging capability. The calculation formula is T=(0.02 / C1+0.1 / C2+0.1 / C3+0.1 / C4+0.1 / C5+0.1 / C6 +0.1 / C7+0.1 / C8)×60.

[0326] (3) Number of cycles

[0327] At 25°C, first charge and discharge the battery for one cycle at 0.1C to activate it. Connect the lithium-ion battery prepared above to a blue electric charge and discharge tester, and then cycle it for a long time at a rate of 0.3C until the ratio of the capacity of the nth cycle to the capacity of the first cycle at 0.3C is less than 80%. The capacity retention rate of the n-1th cycle is defined as 80%, the number of cycles is recorded as n-1, and the test is stopped.

[0328] (4) Storage days

[0329] At 25°C, the battery is capped with a current of 0.33C and recorded as C0. Then the battery is stored at 60°C. After that, the battery is taken out every 7 days and the capacity is tested at room temperature and recorded as C1, C2…C n , to C n The number of days when it is less than or equal to 80% of C0 for the first time is the storage time.

[0330] The above test results are shown in Table 2.

[0331]

[0332]

[0333]

[0334]

[0335] Note: “ / ” in Table 1 means that the condition parameter is not involved in the specific experiment.

[0336] According to Table 1 and Table 2, the specific table decrease rate P0 of the negative electrode sheets obtained in Examples 1-21 is between 12% and 17.8%, the electrode sheet porosity ε is between 18.2% and 25.6%, and the ultimate compaction of the negative electrode sheets can reach 1.8 g.cc -1The lithium-ion battery containing the negative electrode sheet can ensure excellent discharge capacity, fast charging performance and cycle performance, and take into account excellent energy density, cycle performance and storage performance. Specifically, the discharge capacity of the lithium-ion battery can reach more than 358 mAh / g, the discharge capacity can reach less than 20min, and the number of cycles can reach more than 2200. On this basis, the first efficiency can reach more than 90%, and the storage days can reach more than 280 days.

[0337] The inventors have found through research that only by using the negative electrode sheet with a specific specific surface decreasing rate and electrode sheet porosity in the present invention can the lithium-ion battery have excellent discharge capacity, fast charging performance and cycle performance, while taking into account excellent energy density, cycle performance and storage performance. When the specific surface decreasing rate of the negative electrode sheet and the electrode sheet porosity are too large or too small, it is impossible to ensure that the obtained lithium-ion battery has the above-mentioned excellent electrochemical properties.

[0338] Compared with Example 1, the specific surface decrease rate P0 of the negative electrode sheet obtained in Comparative Example 1 is too small, the ultimate compaction of the negative electrode sheet is significantly reduced, the fast charging time of the lithium-ion battery containing it is prolonged, and the discharge capacity, number of cycles, first effect and storage days are significantly deteriorated.

[0339] Compared with Example 1, the specific surface decrease rate P0 of the negative electrode sheet obtained in Comparative Example 2 is too large. Although the ultimate compaction density of the negative electrode sheet is relatively high, and the lithium-ion battery containing it has a relatively high discharge capacity and initial efficiency, the fast charging time of the lithium-ion battery is significantly prolonged, and the number of cycles and storage days are greatly reduced.

[0340] Compared with Example 1, the specific surface decrease rate P0 of the negative electrode sheets obtained in Comparative Examples 3-4 and 6-7 is too small. Although the discharge capacity of the lithium-ion batteries containing them is equivalent, the ultimate compaction density of the negative electrode sheets is significantly reduced, and the fast charging time, number of cycles, first efficiency and storage days of the lithium-ion batteries are significantly deteriorated.

[0341] Compared with Example 1, the specific surface decrease rate P0 of the negative electrode sheet obtained in Comparative Example 5 is too large. Although the ultimate compaction of the negative electrode sheet is equivalent, and the lithium-ion battery containing it has a higher discharge capacity and initial efficiency, the fast charging time of the lithium-ion battery is significantly prolonged, and the number of cycles and storage days are greatly reduced.

[0342] Compared with Example 1, the specific surface decrease rate P0 of the negative electrode sheet obtained in Comparative Example 8 is too large, the ultimate compaction of the negative electrode sheet is significantly reduced, the discharge capacity of the lithium-ion battery containing it is reduced, the fast charging time is greatly extended, and the number of cycles, first effect and storage days are significantly deteriorated.

[0343] Compared with Example 1, the specific surface decrease rate P0 of the negative electrode sheet obtained in Comparative Example 9 is too small. Although the fast charging time and discharge capacity of the obtained lithium-ion battery are equivalent, the ultimate compaction of the negative electrode sheet is significantly reduced, the number of cycles of the lithium-ion battery is greatly reduced, and the first effect and storage days are significantly deteriorated.

[0344] Compared with Example 1, the specific surface decrease rate P0 of the negative electrode sheets obtained in Comparative Examples 10 and 14 is too small, the ultimate compaction density of the negative electrode sheets is significantly reduced, the fast charging time of the lithium-ion batteries containing them is greatly extended, and the discharge capacity, number of cycles, first effect and storage days are significantly deteriorated.

[0345] Compared with Example 1, the specific table decrease rate P0 of the negative electrode sheet obtained in Comparative Examples 11-12 is too large. Although the discharge capacity of the obtained lithium-ion battery is equivalent, the ultimate compaction of the negative electrode sheet is significantly reduced, the fast charging time of the lithium-ion battery is significantly extended, and the number of cycles, first effect and storage days are greatly reduced.

[0346] Compared with Example 1, the specific surface decrease rate P0 of the negative electrode sheet obtained in Comparative Example 13 is too large, the ultimate compaction of the negative electrode sheet is significantly reduced, the discharge capacity of the lithium-ion battery containing it is deteriorated, and the fast charging time, number of cycles, first effect and storage days are all significantly deteriorated.

[0347] Compared with Example 1, the specific surface decrease rate P0 of the negative electrode sheet obtained in Comparative Example 15 is too large. Although the ultimate compaction of the negative electrode sheet and the discharge capacity of the lithium-ion battery are relatively excellent, the fast charging time of the lithium-ion battery is significantly deteriorated, and the number of cycles, first effect and storage days are all significantly deteriorated.

[0348] Compared with Example 1, the specific surface decreasing rate P0 of the negative electrode sheet obtained in Comparative Examples 16-17 is too large, and the porosity of the electrode sheet is If the capacity of the lithium-ion battery is too small, although the discharge capacity of the lithium-ion battery is relatively excellent, the ultimate compression density of the negative electrode sheet is reduced, the fast charging time of the lithium-ion battery is significantly deteriorated, and the number of cycles, first effect and storage days are greatly reduced.

[0349] Compared with Example 1, the specific surface decreasing rate P0 of the negative electrode sheet obtained in Comparative Example 18 is too large, and the porosity of the electrode sheet is If the capacity is too small, although the number of cycles and initial efficiency of the lithium-ion battery are relatively excellent, the ultimate compactness of the negative electrode sheet will be significantly deteriorated, the discharge capacity of the lithium-ion battery will be greatly reduced, the fast charging time will be significantly extended, and the storage days will be significantly reduced.

[0350] Compared with Example 1, the specific surface decrease rate P0 of the negative electrode sheet obtained in Comparative Example 19 is too small, the ultimate compaction of the negative electrode sheet is significantly reduced, the fast charging time of the lithium-ion battery containing it is greatly extended, the discharge capacity and the number of cycles are significantly reduced, and the first effect and storage days are significantly deteriorated.

[0351] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A negative electrode sheet, characterized in that: The specific surface area decrease rate P0 of the negative electrode sheet is 12%-18%; wherein P0=1-P, P is the ratio of the specific surface area of ​​the negative electrode sheet under the second compaction to the specific surface area of ​​the negative electrode sheet under the first compaction; The electrode porosity ε of the negative electrode sheet is greater than 13%, wherein the electrode porosity is the electrode porosity of the negative electrode sheet under the second compaction; The second density is 1.80 g / cc or the ultimate density of the negative electrode sheet; the first density is 1.65 g / cc.

2. The negative electrode sheet according to claim 1, characterized in that: The negative electrode sheet satisfies one or more of the following conditions ac: a. The specific surface decreasing rate of the negative electrode sheet is 13%-17%; b. The porosity of the negative electrode sheet is 18%-26%; c. The bonding force F of the negative electrode sheet N 25-50 N.

3. The negative electrode sheet according to claim 1, characterized in that: The negative electrode sheet includes a negative electrode current collector, a first active material layer is arranged on at least one surface of the negative electrode current collector, a second active material layer is arranged on the first active material layer, the first active material layer includes a first graphite material and a first binder, the second active material layer includes a second graphite material and a second binder, and the Dv50 particle size of the first graphite material is larger than the Dv50 particle size of the second graphite material.

4. The negative electrode sheet according to claim 3, characterized in that: The first graphite material and the second graphite material satisfy one or more of the following conditions ai: a. The difference between the Dv50 particle size of the first graphite material and the Dv50 particle size of the second graphite material is 3-7 μm; b. The particle crushing force F1 of the first graphite material is 30-36 mN; c. The particle crushing force F2 of the second graphite material is 20-30 mN; d. The carbon content of the first graphite material is greater than 99.9%, where the percentage is the mass percentage of the first graphite material; e. The carbon content of the second graphite material is greater than 99.9%, where the percentage is the mass percentage of the first graphite material; f. The Dv50 particle size of the first graphite material is 14-18 μm; g. The Dv50 particle size of the second graphite material is 9-13 μm; h. The first graphite material is a microcrystalline graphite material; i. The second graphite material is a microcrystalline graphite material.

5. The negative electrode sheet according to claim 3, characterized in that: The first active material layer and the second active material layer satisfy one or more of the following conditions ag: a. The content of the first binder is 1.3%-1.8%, where the percentage is the mass percentage of the first active material layer; b. The content of the second binder is 0.7%-1.2%, where the percentage is the mass percentage of the second active material layer; c. The content of the first graphite material is greater than 20%, where the percentage is the mass percentage of the first active material layer; d. The content of the second graphite material is greater than 20%, where the percentage is the mass percentage of the second active material layer; e. The mass ratio of the first active material layer to the second active material layer is 1:(0.4-2.5); f. The thickness of the first active material layer is 50-120 μm; g. The thickness of the second active material layer is 50-110 μm.

6. The negative electrode sheet according to claim 3, characterized in that: The method for preparing the negative electrode sheet comprises the following steps: S1. applying a first negative electrode slurry layer on at least one surface of the negative electrode current collector, wherein the first negative electrode slurry layer comprises a first graphite material and a first binder; S2, applying a second negative electrode slurry layer on the first negative electrode slurry layer, wherein the second negative electrode slurry layer comprises a second graphite material and a second binder; S3, drying, cold pressing, and you are done.

7. The negative electrode sheet according to claim 6, characterized in that: The first negative electrode slurry layer and the second negative electrode slurry layer meet one or more of the following conditions ad: a. The coating density of the first negative electrode slurry layer is greater than 0.055 g / cm 2 ; b. The coating density of the second negative electrode slurry layer is greater than 0.055 g / cm 2 ; c. In step S1, the first graphite material is obtained by pre-treating a first graphite precursor, wherein the pre-treatment includes surface oxidation treatment and / or carboxylation treatment; d. In step S2, the second graphite material is obtained by pre-treating the second graphite precursor, wherein the pre-treatment includes surface oxidation treatment and / or carboxylation treatment.

8. The negative electrode sheet according to claim 7, characterized in that: The first graphite precursor and the second graphite precursor each independently satisfy one or two of the following conditions ab: a. The first graphite precursor and the second graphite precursor each independently satisfy the following conditions: La≤72 nm, Lc≤15 nm; wherein La is the lattice constant at the 110 plane, and Lc is the lattice constant at the 002 plane; F p ≥15 mN, F p is the particle crushing force; b. The preparation methods of the first graphite precursor and the second graphite precursor each independently comprise the following steps: ① A microcrystalline graphite precursor and a binder are first mixed, and a solvent is added to perform a second mixing to obtain a mixture; wherein the temperature of the first mixing is 5-20° C. below the softening point of the binder; ② Pressing the mixture to obtain a microcrystalline graphite blank; ③ laying the microcrystalline graphite rough blank on the surface of the graphitization furnace, laying the graphitized thermal insulation material on the microcrystalline graphite rough blank, and performing graphitization treatment. The microcrystalline graphite rough blank is subjected to graphitization treatment to obtain a microcrystalline graphite embryo body; ④ The microcrystalline graphite embryo is crushed.

9. An electrochemical device, characterized in that: It comprises the negative electrode sheet as claimed in any one of claims 1 to 8.

10. An electronic device, characterized in that: It comprises the electrochemical device as claimed in claim 9.

Citation Information

Patent Citations

  • Mixing process for preparing high-tap-density microcrystalline graphite negative electrode material

    CN110380050A